Event-Related Exchange-Rate Forecasts Combining Information from Betting Quotes and Option Prices - Hanke, Michael; Poulsen, Rolf; Weissensteiner, Alex (Journal of Financial and Quantitative Analysis, 2018)
Betting quotes provide valuable information on market-implied probabilities for outcomes of events such as elections or referendums, which may have an impact on exchange rates. We generate exchange-rate forecasts around such events based on a model that combines risk-neutral event probabilities implied from betting quotes with risk-neutral exchange-rate densities extracted from currency option prices. Its application to predict exchange rates around the Brexit referendum and the U.S. presidential elections shows that these forecasts, conditional on the respective outcomes, were accurate, and markets were able to separate their views on the likelihood and the impact of these events.